Spatial modelling of biodiversity conservation priorities in Portugal's Montado ecosystem using Marxan with Zones. (13th August 2019) - Pinto, Rute; Antunes, Paula; Blumentrath, Stefan; Brouwer, Roy; Clemente, Pedro; Santos, Rui
Summary: Spatial models are increasingly being used to target the most suitable areas for biodiversity conservation. This study investigates how the spatial tool Marxan with Zones (MARZONE) can be used to support the design of cost-effective biodiversity conservation policy. New in this study is the spatial analysis of the costs and effectiveness of different agro-environmental measures (AEMs) for habitat and biodiversity conservation in the Montado ecosystem in Portugal. A distinction is made between the financial costs paid to participating landowners and farmers for adopting AEMs and the broader economic opportunity costs of the corresponding land-use changes. Habitat and species conservation targets are furthermore defined interactively with the local government agency responsible for the management of protected areas, while the costs of agro-forestry activities and alternative land uses are estimated in direct consultation with local landowners. MARZONE identifies the spatial distribution of priority areas for conservation and the associated costs, some of which overlap with existing protected areas. These results provide useful insights into the trade-offs between nature conservation and the opportunity costs of protecting ecologically vulnerable areas, helping to improve current and future conservation policy design.